2015
DOI: 10.1371/journal.pgen.1005494
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in Centromeric Histone Induce Post-zygotic Incompatibility and Uniparental Inheritance

Abstract: The centromeric histone 3 variant (CENH3, aka CENP-A) is essential for the segregation of sister chromatids during mitosis and meiosis. To better define CENH3 functional constraints, we complemented a null allele in Arabidopsis with a variety of mutant alleles, each inducing a single amino acid change in conserved residues of the histone fold domain. Many of these transgenic missense lines displayed wild-type growth and fertility on self-pollination, but exhibited frequent post-zygotic death and uniparental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
139
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(147 citation statements)
references
References 53 publications
(61 reference statements)
8
139
0
Order By: Relevance
“…In future, choice of better promoter for RNAi silencing and evaluation of more events could yield efficient HI lines of B. juncea . Recently, it has been shown that single amino acid change in HFD is sufficient to induce haploids in A. thaliana (Karimi-Ashtiyani et al, 2015; Kuppu et al, 2015) albeit at considerably low frequency. However, in such cases also, complete loss or replacement of native CENH3 was essential.…”
Section: Discussionmentioning
confidence: 99%
“…In future, choice of better promoter for RNAi silencing and evaluation of more events could yield efficient HI lines of B. juncea . Recently, it has been shown that single amino acid change in HFD is sufficient to induce haploids in A. thaliana (Karimi-Ashtiyani et al, 2015; Kuppu et al, 2015) albeit at considerably low frequency. However, in such cases also, complete loss or replacement of native CENH3 was essential.…”
Section: Discussionmentioning
confidence: 99%
“…MiMe combined with genome elimination indeed leads to clonal offspring, as previously demonstrated in Arabidopsis [13]. However, the CENH3 manipulation used in Arabidopsis to provoke genome elimination has not been transferred in other species to date [20,[39][40][41], except in maize but with a lower frequency [42]. The frequency of genome elimination can be genetically controlled in cereals, notably in maize [43][44][45].…”
Section: Discussionmentioning
confidence: 71%
“…Ravi and Chan (2010) described a novel method of in vivo haploid induction through centromere-mediated genome elimination in Arabidopsis based on CENH3. CENH3 consists of an N-terminal tail region, which is highly variable even between closely related species, and a C- terminal Histone Fold Domain (HFD), which is well conserved across species (Britt and Kuppu, 2016;Kuppu et al, 2015;Malik and Henikoff, 2003). The N-terminal tail has one alpha helix (aN), and the HFD domain has three alpha helices separated by two loop regions (a1-L1-a2-L2-a3) Watts et al, 2016).…”
Section: Haploidization Via Centromere-mediated Chromosome Eliminationmentioning
confidence: 99%
“…When pollinated with wild-type plants, Atcenh3 L130F-1 induced haploids and aneuploids which may attribute to the less total CENH3 protein than wild-type plants. In parallel, Kuppu et al (2015) conducted complementation tests on cenh3-1 with a variety of mutant CENH3s that each has single amino acid substitution in HFD conserved residues. The mutant CENH3s with single amino acid changes P82S, G83E, A132T, A136T and A86V exhibited no significant effect in the process of meiosis or mitosis and gave normal progenies on self-pollination, while inducing postzygotic incompatibility and low frequency of paternal haploids when outcrossing to wild-type plants.…”
Section: Haploidization Via Centromere-mediated Chromosome Eliminationmentioning
confidence: 99%